2017
DOI: 10.1021/acs.analchem.7b00408
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Accurate-Mass Mass Spectrometry Enabling In-Depth Characterization of in Vivo Biotransformations for Intact Antibody-Drug Conjugates

Abstract: Antibody-drug conjugates (ADCs) represent a promising class of therapeutics for the targeted delivery of highly potent cytotoxic drugs to tumor cells to improve bioactivity while minimizing side effects. ADCs are composed of both small and large molecules and therefore have complex molecular structures. In vivo biotransformations may further increase the complexity of ADCs, representing a unique challenge for bioanalytical assays. Quadrupole-time-of-flight mass spectrometry (Q-TOF MS) with electrospray ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Therefore, this approach is primarily applicable for ADCs with conjugation sites located in the Fab region. The second strategy was to analyze ADCs in the intact form using HR/AM Orbitrap MS, 16 which preserves the structural information of ADCs as much as possible with minimal treatment. This approach has broader applications, being suitable for ADCs with site-specific conjugations in both Fab and Fc regions, as well as for ADCs with random lysine conjugations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this approach is primarily applicable for ADCs with conjugation sites located in the Fab region. The second strategy was to analyze ADCs in the intact form using HR/AM Orbitrap MS, 16 which preserves the structural information of ADCs as much as possible with minimal treatment. This approach has broader applications, being suitable for ADCs with site-specific conjugations in both Fab and Fc regions, as well as for ADCs with random lysine conjugations.…”
Section: Discussionmentioning
confidence: 99%
“…The cysteine adducts have a greater abundance than the glutathione adduct ( Figure 3), which is consistent with a previous observation for a disulfide-linked PBD dimer TDC. 16 This may be attributed to the higher concentration of reduced cysteine in plasma. 17,18 Examination of the rest of the peaks within this mass range is discussed in the following section.…”
Section: T-dm1 Undergoes Loss Of Dm1 Drug In Circulation Via Maleimidmentioning
confidence: 99%
See 1 more Smart Citation
“…Grafmuller et al used IAC combined with HRMS to reveal the DAR for in vivo monkey ADC samples (Grafmuller et al, ). He et al demonstrated that, with the higher resolving power of MS, small mass changes (deacetylation on the payload) at the level of intact ADCs can be resolved (He et al, ). Tumey et al later reviewed the in vivo biotransformation of ADC and stated that HRMS combined with IAC for intact protein analysis played critical roles in the characterization and semi‐quantitation of ADCs in biological matrices (Tumey et al, ).…”
Section: Intact Bioanalysis Of Proteinsmentioning
confidence: 99%
“…Over the last decade, liquid chromatography coupled with mass spectrometry (LC-MS), has emerged as an appealing technology for therapeutic protein bioanalysis, complementing traditional LBAs [18,19]. Nevertheless, there are also significant challenges in isolating, concentrating, detecting and quantifying specific proteins by LC-MS in the presence of the overwhelming abundance of endogenous proteins found in biological matrices.…”
Section: Application Of Lc-ms Technologiesmentioning
confidence: 99%